在归属与抗议之间的“抵抗之仪” ——读白瑨的《归属之仪: 马来西亚槟城华人社群的记忆、现代性与身分认同》: “Rites of Resistance” Between Belonging and Protest Review of Jean DeBernardi’s Rites of Belonging: Memory, Modernity and Identity in a Malaysia Chinese Community - Loi, Chen Hwee (ERUDITE: Journal of Chinese Studies and Education, 2024)
有别于历史人类学的视角，以及笔者专业的限制，本文尝试以当代儒家研究者所关切的课题来参阅本书，或可提供另一种阅读角度，意即：儒家的礼仪和谐观如何与歧见共存，甚至在必要时，“抗议之礼仪”（rituals of protest）是如何可能的。《归属之仪》为我们展示了代代马来西亚华人归属斯土之恳望，但是，华人于斯土仍旧是“归属”不得且“抗议”无力时，“抵抗”才更符合进退不得的生活现实，也因此，本文将此题名为“抵抗之仪”来展开。本文拟从两方面来阅读：1. 礼仪实践的必要及其目的、2. “抵抗之仪”的局限；前者梳理该书关涉到礼仪实践的脉络，后者则是在前者的基础上进行审思。Unlike the perspective of historical anthropology and the constraints of one's own profession, this review attempts to refer to this book in terms of a subject of concern to contemporary Confucian researchers, which may provide an alternative reading, namely: how can a harmonious view of rituals coexist with disagreement in a Confucian perspective? And even, if necessary, how "rituals of protest" are possible. Rites of Belonging shows us the aspirations of the Malaysian Chinese to belong to the land, but the situation of the Malaysian Chinese is still one in which neither belonging nor protesting is possible, but resistance is more in line with the realities of life, which is why this review is titled "rituals of resistance". The review is intended to be read from two perspectives: 1) the necessity and purpose of rites, and 2) the limitations of the "rituals of resistance"; the former organizes this book about the practice of rituals, while the latter is a reflection on it.Keywords: Ritual practice, Rituals of protest, Accommodation of disagreement